Mathematical literacy ability of 8th graders in Problem Based Learning with Think Talk Write approach - Warniatun, Warniatun; Junaedi, Iwan (Department of Mathematics, Universitas Negeri Semarang, 2020)
The purposes of this study were to explore how the Problem-Based Learning model with the Think Talk Write approach affect mathematical literacy ability. This study used mixed methods with concurrent embedded models. The subjects of this study were a class in a Junior High School in Margasari. Observation, documentation, tests, and interviews were used to collect data. The design used in this study was a randomized pretest-posttest control group design. The method of data collection in this study is the method of documentation, tests, observation, and interviews. The purpose of the interview is to find out students' mathematical literacy abilities. The data analysis in this study was an analysis of the initial data test, analysis of the results of tests of mathematical literacy ability, and qualitative data analysis. Test data includes the normality and homogeneity test. The normality was checked using the Kolmogorov-Smirnov Test, the homogeneity was checked using the Levene test, and the similarities between the two class was checked using the Independent-Sample T-Test. The students' mathematical literacy abilities were analyzed based on the results of the post-test using the Miles and Huberman Model. The study revealed the profile of mathematics literacy abilities of students in the setting of Problem-Based Learning.